Preparing clinicians to be site investigators in multicenter clinical trials: A training program at an academic medical center - Loucks, Tammy L.; Lee-Chavarria, Diana; Harvey, Jillian; Paranal, Rechelle; Denmark, Signe; Flume, Patrick A.; Chimowitz, Marc; Turan, Tanya N. (Journal of clinical and translational science, 2023)
Clinical trials are essential in the translation of biomedical discoveries to new clinical interventions and therapeutics. Successful multisite clinical trials require qualified site investigators with an understanding of the full spectrum of processes and requirements from trial identification through closeout. New site investigators may be deterred by competing demands on their time, the complexity of administrative and regulatory processes for trial initiation and conduct, and limited access to experienced mentor networks. We established a Clinical Trialist Training Program (CTTP) and complimentary Clinical Trials Bootcamp at our institution to address these barriers and increase the number of local site investigators enabled to lead successful clinical trials. An initial cohort of four CTTP scholars received salary support with protected time, didactic training, assistance with study identification and start-up navigation, and quarterly progress meetings. By the end of the 12-month program, this initial cohort identified 33 new trials, utilized feasibility assessments, and reported being on target to sustain their protected time from new clinical trials. Bootcamp attendees demonstrated increased knowledge of resources, offices, and processes associated with clinical trial conduct. Our results support providing compensated protected time, training, and access to experienced clinical research professionals to enable clinicians to become successful site investigators.